A large-scale galaxy structure at z = 2.02 associated with the radio galaxy MRC 0156-252 - Galametz, A.; Stern, D.; Pentericci, L.; De Breuck, C.; Vernet, J.; Wylezalek, D.; Fassbender, R.; Hatch, N.; Kurk, J.; Overzier, R.; Rettura, A.; Seymour, Nick (2013)
We present the spectroscopic confirmation of a structure of galaxies surrounding the radio galaxy MRC 0156-252 at z = 2.02. The structure was initially discovered as an overdensity of both near-infrared selected z > 1.6 and mid-infrared selected z > 1.2 galaxy candidates. We used the VLT/FORS2 multi-object spectrograph to target ~80 high-redshift galaxy candidates, and obtain robust spectroscopic redshifts for more than half the targets. The majority of the confirmed sources are star-forming galaxies at z > 1.5. In addition to the radio galaxy, two of its close-by companions (<6″) also show AGN signatures. Ten sources, including the radio galaxy, lie within | z − 2.020 | <0.015 (i.e., velocity offsets <1500 km s-1) and within projected 2 Mpc comoving of the radio galaxy. Additional evidence suggests not only that the galaxy structure associated with MRC 0156-252 is a forming galaxy cluster but also that this structure is most probably embedded in a larger-scale structure.